The Discrepancy between Observed and Predicted Heliospheric Energetic Neutral Atoms below Solar Wind Energy ... - Galli, André; Baliukin, Igor I.; Kornbleuth, Marc; Opher, Merav; Fuselier, Stephen A.; Sokół, Justyna M.; Dialynas, Konstantinos; Dayeh, Maher A.; Izmodenov, Vladislav V.; Richardson, John D. (Institute of Physics Publishing IOP, 2023)
Measuring energetic neutral atoms (ENAs) allows for the remote observation of ion populations from the frontiers of our heliosphere. In this study, we compare the ENAs observed with the IBEX-Lo instrument onboard the Interstellar Boundary Explorer with ENA predictions from two heliosphere models. In contrast to previous studies, this paper presents model-data comparisons for the energy range 50 eV–2 keV over one full solar cycle not only in the upwind direction (Voyager 1 and Voyager 2 sky directions), but also for the north pole, south pole, port tail lobe, and downwind directions. The two heliosphere models produce the same basic result: there is a large gap (1 to 2 orders of magnitude in ENA intensity at 100 eV) between ENA data and model predictions between 100 and 500 eV for all sky directions. The reason for this gap is not understood yet. While some explanations are plausible and will be investigated in future studies, other explanations are excluded. ...